Preparation method of formaldehyde-free high-performance vegetable protein adhesive
By adding plant-based bacterial dehydrating agent and nano zinc oxide to the deld-free plant protein adhesive, combined with the silane coupling agent KH-550, the antibacterial and durability problems of adhesives are solved, and higher antibacterial, water resistance and adhesive properties are achieved, and service life and storage life are extended.
Patent Information
- Application Number
- CN202411836513.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
The existing legacy-free plant protein adhesives lack effective antibacterial measures and are prone to degradation under humid environments or ultraviolet irradiation, affecting their service life and stability.
The antibacterial properties are enhanced through natural ingredients such as tea polyphenols, aloe vera extract, honeysuckle extract, etc., and the adhesive strength and durability are improved through the silane coupling agent KH-550.
It significantly improves the antibacterial properties, water resistance and adhesive strength of the adhesive, extends the service life and storage period, and enhances market competitiveness.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and specifically relates to a method for preparing an aldehyde-free high-performance plant protein adhesive. Background Art
[0002] Formaldehyde-free plant protein adhesive is a highly environmentally friendly adhesive material made from plant protein through a special process. It does not contain formaldehyde and other harmful volatile organic compounds and is an ideal green and environmentally friendly adhesive. The main raw materials of plant protein adhesives come from proteins from crops such as soybeans and corn. After physical or chemical modification, these proteins can exert good bonding properties. Due to its non-toxic, odorless and non-volatile properties, formaldehyde-free plant protein adhesives are widely used in furniture, panels, wood processing, building decoration and other fields, especially in the preparation of environmentally friendly artificial panels and wood composite materials. With the increasing awareness of environmental protection and the pursuit of healthy life, traditional formaldehyde-containing adhesives are gradually eliminated by the market due to their release of harmful substances, and formaldehyde-free high-performance plant protein adhesives have therefore come into being.
[0003] However, the existing formaldehyde-free plant protein adhesives lack effective antibacterial measures, making the adhesive vulnerable to microbial attack in humid or easily contaminated environments, affecting its service life and stability. In addition, traditional plant protein adhesives are prone to degradation under ultraviolet radiation and have poor weather resistance, which limits their application in outdoor or long-term use scenarios. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an aldehyde-free high-performance plant protein adhesive in order to solve the above-mentioned problems.
[0005] The technical solution adopted by the present invention is as follows: a method for preparing an aldehyde-free high-performance plant protein adhesive, the method comprising the following steps:
[0006] S1: First, weigh the raw materials for preparation, and weigh: plant soybean protein powder: 100 parts by weight; water: 200-250 parts by weight; glycerin: 10-20 parts by weight; sodium hydroxide: 1-2 parts by weight; calcium carbonate: 20-30 parts by weight; urea: 5-10 parts by weight; sodium benzoate: 1-2 parts by weight; polyvinyl alcohol: 5-10 parts by weight; citric acid: 1-2 parts by weight; hyaluronic acid: 1-5 parts by weight; silane coupling agent KH-550: 1-3 parts by weight; nano zinc oxide: 1-5 parts by weight and plant-based fungicide 11-15 parts by weight;
[0007] S2: Mix plant soy protein powder and water in proportion, use a high-speed mixer to stir until a uniform, particle-free protein suspension is formed, slowly add glycerol to the protein suspension, use a low-speed mixer to stir, ensure that the glycerol is completely integrated into the protein solution, and enhance the flexibility of the colloid;
[0008] S3: slowly dripping sodium hydroxide solution into the above mixed solution, monitoring the pH value at the same time, adjusting it to the alkaline range, and then standing to react for 15 minutes;
[0009] S4: adding calcium carbonate to the mixed solution after the reaction, and stirring with a high-speed stirrer until the calcium carbonate is evenly dispersed to form a stable suspension system;
[0010] S5: adding urea, stirring with a medium-speed mixer and heating at the same time, promoting the reaction between urea and protein, and enhancing the water resistance of the adhesive;
[0011] S6: After the mixed solution is cooled to room temperature, sodium benzoate and polyvinyl alcohol are added, and stirred using a high-speed stirrer until they are completely dissolved to form a uniform colloid;
[0012] S7: Add hyaluronic acid to the colloid and stir with a low-speed mixer to ensure that the hyaluronic acid is evenly distributed and improve the water retention performance of the adhesive;
[0013] S8: adding silane coupling agent KH-550 and nano zinc oxide, stirring with a high-speed mixer to ensure that the coupling agent and nano zinc oxide are fully dispersed to enhance the bonding strength and antibacterial properties of the adhesive;
[0014] S9: Finally, add citric acid to adjust the pH value to neutral or slightly alkaline, use a low-speed mixer to stir for 5 minutes to ensure that the pH of the solution is stable, and then let it stand until the bubbles are eliminated to obtain the finished formaldehyde-free high-performance plant protein adhesive.
[0015] In a preferred embodiment, in step S1, the plant-based disinfectant includes: tea polyphenols: 15 parts by weight; aloe extract: 15 parts by weight; hyaluronic acid: 5 parts by weight; glycerin: 5 parts by weight; lavender oil: 2 parts by weight; peppermint oil: 1 part by weight; honeysuckle extract: 10 parts by weight; lemongrass oil: 2 parts by weight; antibacterial silver ions: 1-3 parts by weight; xanthan gum: 1-2 parts by weight; deionized water: 115 parts by weight;
[0016] The preparation method includes: preheating deionized water to 40-50°C; adding xanthan gum, glycerin and hyaluronic acid in sequence, and stirring evenly until completely dissolved; adding tea polyphenols, aloe extract and honeysuckle extract, and continuing to stir until evenly distributed; adding antibacterial ions to ensure that they are completely dispersed in the solution; finally adding lavender oil, peppermint oil and lemongrass oil, stirring evenly and cooling to room temperature; after passing the quality inspection, packaging for use, and obtaining a plant-based disinfectant.
[0017] In a preferred embodiment, in step S2, after the protein suspension is prepared, glycerol is slowly poured into the suspension, and stirred at a speed of 300-500 rpm for 10 minutes using a low-speed stirrer; the temperature is maintained between 25-30°C during the stirring process.
[0018] In a preferred embodiment, in step S3, after the sodium hydroxide solution is formed, it is slowly dripped into the mixed solution in step S2, and the pH value is monitored using a pH meter to adjust to the alkaline range of pH 10-11; during the dripping process, a low-speed stirrer is used to stir at a speed of 200-300 rpm to ensure that the solution is evenly mixed; after the dripping is completed, the reaction is allowed to stand for 15 minutes to allow the solution to fully react.
[0019] In a preferred embodiment, in step S4, calcium carbonate is slowly poured into the mixed solution after the reaction, and stirred at a speed of 1000-1500 rpm for 20 minutes using a high-speed stirrer; during the stirring process, the temperature is maintained between 30-35° C. to ensure that the calcium carbonate is evenly dispersed to form a stable suspension system.
[0020] In a preferred embodiment, in step S5, urea is slowly poured into the mixed solution, and stirred at a speed of 500-700 rpm for 10 minutes using a medium-speed mixer; at the same time, the mixture is heated to 50-60°C to promote the reaction between urea and protein to form a urea-protein complex, thereby enhancing the water resistance of the adhesive.
[0021] In a preferred embodiment, in step S6, after the mixed solution is cooled to room temperature, sodium benzoate and polyvinyl alcohol are slowly poured into the mixed solution, and stirred at a speed of 1000-1500 rpm for 15 minutes using a high-speed stirrer.
[0022] In a preferred embodiment, in step S7, a low-speed mixer is used to stir at a speed of 300-500 rpm for 5 minutes to ensure that the hyaluronic acid is evenly distributed and the water retention performance of the adhesive is improved; during the stirring process, pay attention to maintaining the temperature between 25-30°C.
[0023] In a preferred embodiment, in step S8, a high-speed stirrer is used to stir at a speed of 1000-1500 rpm for 20 minutes to ensure that the coupling agent and nano zinc oxide are fully dispersed to form a stable nano-composite material, and the temperature is maintained between 30-35°C during the stirring process.
[0024] In a preferred embodiment, in step S9, citric acid is slowly poured into the colloid and then stirred at a speed of 200-300 rpm for 5 minutes using a low-speed stirrer; meanwhile, a pH meter is used to monitor the pH value and the pH value is adjusted to a neutral or slightly alkaline pH of 7-8.
[0025] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0026] 1. In the present invention, the addition of plant-based bactericide brings significant beneficial effects to the formaldehyde-free high-performance plant protein adhesive. First, the tea polyphenols, aloe extract, honeysuckle extract and antibacterial silver ions in the bactericide give the adhesive excellent antibacterial properties, effectively inhibit the growth of bacteria and mold, and extend the service life of the adhesive. At the same time, the moisturizing effect of hyaluronic acid and glycerol improves the water resistance of the adhesive, ensuring that it can still maintain a stable bonding effect in a humid environment. In addition, the thickening effect of xanthan gum enhances the bonding strength of the adhesive, making it more firm during application.
[0027] 2. In the present invention, the natural plant extracts and essential oil components in the plant-based fungicide not only improve the environmental friendliness of the adhesive, but also bring it a natural fragrance and improve the user experience. By reducing the use of chemical additives, the fungicide reduces potential health risks and makes the adhesive safer and more reliable. On the whole, the addition of plant-based fungicide not only improves the comprehensive properties of the formaldehyde-free high-performance plant protein adhesive, such as antibacterial, water resistance, bonding strength and flexibility, but also extends its storage life, enhances its market competitiveness, and brings a more environmentally friendly, healthy and efficient choice to the adhesive industry.
[0028] 3. In the present invention, the addition of silane coupling agent KH-550 has a significant improvement effect on the formaldehyde-free high-performance plant protein adhesive. First, KH-550 can effectively enhance the interfacial bonding force between the adhesive and the substrate. Through its unique chemical structure, it forms a strong chemical bond between the plant protein molecules and the surface of the substrate, thereby greatly improving the bonding strength and durability of the adhesive. In addition, KH-550 also has good dispersibility, which can promote the uniform distribution of fillers such as calcium carbonate in the adhesive, avoid agglomeration, and further optimize the mechanical properties and construction performance of the adhesive. Therefore, the introduction of the silane coupling agent KH-550 enables the plant protein adhesive to exhibit better bonding effect and stability in a variety of complex application environments.
[0029] 4. In the present invention, the addition of nano zinc oxide brings additional functions and performance improvements to the formaldehyde-free high-performance plant protein adhesive. On the one hand, nano zinc oxide has excellent antibacterial properties, can effectively inhibit the microbial contamination that may occur during the use of the adhesive, and prolong the service life and storage stability of the adhesive. On the other hand, the ultraviolet shielding effect of nano zinc oxide protects the adhesive from the influence of ultraviolet radiation, reduces the degradation reaction caused by ultraviolet rays, and thus enhances the weather resistance and aging resistance of the adhesive. In addition, the nano size effect of nano zinc oxide may also have a positive effect on the mechanical properties of the adhesive, such as improving its hardness and wear resistance. In summary, the addition of nano zinc oxide not only improves the antibacterial and weather resistance of the plant protein adhesive, but also has a beneficial effect on its long-term stability and mechanical properties, enabling it to exhibit more outstanding performance in a wider range of application fields. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] Embodiment 1:
[0032] A method for preparing an aldehyde-free high-performance plant protein adhesive, the method comprising the following steps:
[0033] S1: First, weigh the raw materials for preparation, and weigh 100 parts by weight of plant soybean protein powder; 200 parts by weight of water; 10 parts by weight of glycerol; 1 part by weight of sodium hydroxide; 20 parts by weight of calcium carbonate; 5 parts by weight of urea; 1 part by weight of sodium benzoate; 5 parts by weight of polyvinyl alcohol; 1 part by weight of citric acid; 1 part by weight of hyaluronic acid; 1 part by weight of silane coupling agent KH-550; 1 part by weight of nano zinc oxide and 11 parts by weight of plant-based fungicide;
[0034] S2: Mix plant soy protein powder and water in proportion, use a high-speed blender to stir until a uniform, particle-free protein suspension is formed, slowly add glycerin to the protein suspension, use a low-speed blender to stir, and ensure that the glycerin is completely integrated into the protein solution to enhance the flexibility of the colloid.
[0035] S3: Slowly drip the sodium hydroxide solution into the above mixed solution, monitor the pH value at the same time, adjust it to the alkaline range, and then let it react for 15 minutes.
[0036] S4: Add calcium carbonate to the reaction mixture and stir with a high-speed stirrer until the calcium carbonate is evenly dispersed to form a stable suspension system
[0037] S5: Add urea and use a medium-speed mixer to stir and heat at the same time to promote the reaction between urea and protein and enhance the water resistance of the adhesive.
[0038] S6: After the mixed solution is cooled to room temperature, sodium benzoate and polyvinyl alcohol are added and stirred with a high-speed mixer until they are completely dissolved to form a uniform colloid.
[0039] S7: Add hyaluronic acid to the colloid and use a low-speed mixer to ensure that the hyaluronic acid is evenly distributed to improve the water retention performance of the adhesive.
[0040] S8: Add silane coupling agent KH-550 and nano zinc oxide, and stir with a high-speed mixer to ensure that the coupling agent and nano zinc oxide are fully dispersed to enhance the bonding strength and antibacterial properties of the adhesive.
[0041] S9: Finally, add citric acid to adjust the pH value to neutral or slightly alkaline, use a low-speed mixer to stir for 5 minutes to ensure that the pH of the solution is stable, and then let it stand until the bubbles are eliminated to obtain the finished formaldehyde-free high-performance plant protein adhesive.
[0042] In step S1, the plant-based disinfectant includes: tea polyphenols: 15 parts by weight; aloe extract: 15 parts by weight; hyaluronic acid: 5 parts by weight; glycerin: 5 parts by weight; lavender oil: 2 parts by weight; peppermint oil: 1 part by weight; honeysuckle extract: 10 parts by weight; lemongrass oil: 2 parts by weight; antibacterial silver ions: 1-3 parts by weight; xanthan gum: 1-2 parts by weight; deionized water: 115 parts by weight;
[0043] The preparation method includes: preheating deionized water to 40-50°C; adding xanthan gum, glycerin and hyaluronic acid in sequence, and stirring evenly until completely dissolved; adding tea polyphenols, aloe extract and honeysuckle extract, and continuing to stir until evenly distributed; adding antibacterial ions to ensure that they are completely dispersed in the solution; finally adding lavender oil, peppermint oil and lemongrass oil, stirring evenly and cooling to room temperature; after passing the quality inspection, packaging for use, and obtaining a plant-based disinfectant.
[0044] In step S2, after the protein suspension is prepared, glycerol is slowly poured into the suspension and stirred at 300-500 rpm for 10 minutes using a low-speed stirrer. During the stirring process, pay attention to keeping the temperature between 25-30°C to avoid excessively high or low temperatures that affect the integration of glycerol. Ensure that glycerol is completely integrated into the protein solution and observe that the liquid becomes smoother to enhance the flexibility of the colloid.
[0045] In the step S3, after forming a sodium hydroxide solution, it is slowly dripped into the mixed solution in step S2, and the pH value is monitored using a pH meter and adjusted to an alkaline range (pH 10-11). During the dropwise addition, a low-speed stirrer is used to stir at a speed of 200-300 rpm to ensure that the solution is evenly mixed. After the dropwise addition is completed, the reaction is allowed to stand for 15 minutes to allow the solution to fully react.
[0046] In step S4, calcium carbonate is slowly poured into the mixed solution after the reaction, and stirred at a speed of 1000-1500 rpm for 20 minutes using a high-speed stirrer. During the stirring process, the temperature is maintained between 30-35° C. to ensure that the calcium carbonate is evenly dispersed to form a stable suspension system. The liquid is observed to become slightly thick to enhance the bonding strength of the adhesive.
[0047] In step S5, urea is slowly poured into the mixed solution, and stirred at a speed of 500-700 rpm for 10 minutes using a medium-speed mixer. At the same time, the mixture is heated to 50-60°C to promote the reaction between urea and protein, form a urea-protein complex, and enhance the water resistance of the adhesive. During the heating process, pay attention to controlling the temperature to avoid excessively high temperatures that may cause protein denaturation.
[0048] In step S6, after the mixed solution is cooled to room temperature, sodium benzoate and polyvinyl alcohol are slowly poured into the mixed solution, and stirred at a speed of 1000-1500 rpm for 15 minutes using a high-speed stirrer. Ensure that the sodium benzoate and polyvinyl alcohol are completely dissolved to form a uniform colloid. Observe that the liquid becomes more viscous to enhance the stability and viscosity of the adhesive.
[0049] In step S7, a low-speed mixer is used to stir at a speed of 300-500 rpm for 5 minutes to ensure that the hyaluronic acid is evenly distributed and improve the water retention performance of the adhesive. During the stirring process, pay attention to maintaining the temperature between 25-30° C. to avoid too high or too low a temperature that affects the effect of the hyaluronic acid.
[0050] In step S8, a high-speed stirrer is used to stir at a speed of 1000-1500 rpm for 20 minutes to ensure that the coupling agent and nano zinc oxide are fully dispersed to form a stable nano composite material and enhance the bonding strength and antibacterial properties of the adhesive. During the stirring process, the temperature is maintained between 30-35° C. and the liquid is observed to become more uniform.
[0051] In step S9, citric acid is slowly poured into the colloid and stirred at a speed of 200-300 rpm for 5 minutes using a low-speed stirrer. At the same time, a pH meter is used to monitor the pH value and adjusted to neutral or slightly alkaline (pH 7-8). Ensure that the pH of the solution is stable to avoid excessively high or low pH values affecting the performance of the adhesive. After the adjustment is completed, stand for 30 minutes, and the finished product, aldehyde-free high-performance plant protein adhesive, can be obtained after the bubbles are eliminated. During the standing process, pay attention to avoid air contact and maintain the sealing of the container.
[0052] Embodiment 2:
[0053] A method for preparing an aldehyde-free high-performance plant protein adhesive, the method comprising the following steps:
[0054] S1: First, weigh the raw materials for preparation, and weigh: plant soybean protein powder: 100 parts by weight; water: 250 parts by weight; glycerol: 20 parts by weight; sodium hydroxide: 2 parts by weight; calcium carbonate: 30 parts by weight; urea: 10 parts by weight; sodium benzoate: 2 parts by weight; polyvinyl alcohol: 10 parts by weight; citric acid: 2 parts by weight; hyaluronic acid: 5 parts by weight; silane coupling agent KH-550: 3 parts by weight; nano zinc oxide: 5 parts by weight and plant-based fungicide 15 parts by weight;
[0055] S2: Mix plant soy protein powder and water in proportion, use a high-speed blender to stir until a uniform, particle-free protein suspension is formed, slowly add glycerin to the protein suspension, use a low-speed blender to stir, and ensure that the glycerin is completely integrated into the protein solution to enhance the flexibility of the colloid.
[0056] S3: Slowly drip the sodium hydroxide solution into the above mixed solution, monitor the pH value at the same time, adjust it to the alkaline range, and then let it react for 15 minutes.
[0057] S4: Add calcium carbonate to the reaction mixture and stir with a high-speed stirrer until the calcium carbonate is evenly dispersed to form a stable suspension system
[0058] S5: Add urea and use a medium-speed mixer to stir and heat at the same time to promote the reaction between urea and protein and enhance the water resistance of the adhesive.
[0059] S6: After the mixed solution is cooled to room temperature, sodium benzoate and polyvinyl alcohol are added and stirred with a high-speed mixer until they are completely dissolved to form a uniform colloid.
[0060] S7: Add hyaluronic acid to the colloid and use a low-speed mixer to ensure that the hyaluronic acid is evenly distributed to improve the water retention performance of the adhesive.
[0061] S8: Add silane coupling agent KH-550 and nano zinc oxide, and stir with a high-speed mixer to ensure that the coupling agent and nano zinc oxide are fully dispersed to enhance the bonding strength and antibacterial properties of the adhesive.
[0062] S9: Finally, add citric acid to adjust the pH value to neutral or slightly alkaline, use a low-speed mixer to stir for 5 minutes to ensure that the pH of the solution is stable, and then let it stand until the bubbles are eliminated to obtain the finished formaldehyde-free high-performance plant protein adhesive.
[0063] In step S1, the plant-based disinfectant includes: tea polyphenols: 15 parts by weight; aloe extract: 15 parts by weight; hyaluronic acid: 5 parts by weight; glycerin: 5 parts by weight; lavender oil: 2 parts by weight; peppermint oil: 1 part by weight; honeysuckle extract: 10 parts by weight; lemongrass oil: 2 parts by weight; antibacterial silver ions: 1-3 parts by weight; xanthan gum: 1-2 parts by weight; deionized water: 115 parts by weight;
[0064] The preparation method includes: preheating deionized water to 40-50°C; adding xanthan gum, glycerin and hyaluronic acid in sequence, and stirring evenly until completely dissolved; adding tea polyphenols, aloe extract and honeysuckle extract, and continuing to stir until evenly distributed; adding antibacterial ions to ensure that they are completely dispersed in the solution; finally adding lavender oil, peppermint oil and lemongrass oil, stirring evenly and cooling to room temperature; after passing the quality inspection, packaging for use, and obtaining a plant-based disinfectant.
[0065] In step S2, after the protein suspension is prepared, glycerol is slowly poured into the suspension and stirred at 300-500 rpm for 10 minutes using a low-speed stirrer. During the stirring process, pay attention to keeping the temperature between 25-30°C to avoid excessively high or low temperatures that affect the integration of glycerol. Ensure that glycerol is completely integrated into the protein solution and observe that the liquid becomes smoother to enhance the flexibility of the colloid.
[0066] In the step S3, after forming a sodium hydroxide solution, it is slowly dripped into the mixed solution in step S2, and the pH value is monitored using a pH meter and adjusted to an alkaline range (pH 10-11). During the dropwise addition, a low-speed stirrer is used to stir at a speed of 200-300 rpm to ensure that the solution is evenly mixed. After the dropwise addition is completed, the reaction is allowed to stand for 15 minutes to allow the solution to fully react.
[0067] In step S4, calcium carbonate is slowly poured into the mixed solution after the reaction, and stirred at a speed of 1000-1500 rpm for 20 minutes using a high-speed stirrer. During the stirring process, the temperature is maintained between 30-35° C. to ensure that the calcium carbonate is evenly dispersed to form a stable suspension system. The liquid is observed to become slightly thick to enhance the bonding strength of the adhesive.
[0068] In step S5, urea is slowly poured into the mixed solution, and stirred at a speed of 500-700 rpm for 10 minutes using a medium-speed mixer. At the same time, the mixture is heated to 50-60°C to promote the reaction between urea and protein, form a urea-protein complex, and enhance the water resistance of the adhesive. During the heating process, pay attention to controlling the temperature to avoid excessively high temperatures that may cause protein denaturation.
[0069] In step S6, after the mixed solution is cooled to room temperature, sodium benzoate and polyvinyl alcohol are slowly poured into the mixed solution, and stirred at a speed of 1000-1500 rpm for 15 minutes using a high-speed stirrer. Ensure that the sodium benzoate and polyvinyl alcohol are completely dissolved to form a uniform colloid. Observe that the liquid becomes more viscous to enhance the stability and viscosity of the adhesive.
[0070] In step S7, a low-speed mixer is used to stir at a speed of 300-500 rpm for 5 minutes to ensure that the hyaluronic acid is evenly distributed and improve the water retention performance of the adhesive. During the stirring process, pay attention to maintaining the temperature between 25-30° C. to avoid too high or too low a temperature that affects the effect of the hyaluronic acid.
[0071] In step S8, a high-speed stirrer is used to stir at a speed of 1000-1500 rpm for 20 minutes to ensure that the coupling agent and nano zinc oxide are fully dispersed to form a stable nano composite material and enhance the bonding strength and antibacterial properties of the adhesive. During the stirring process, the temperature is maintained between 30-35° C. and the liquid is observed to become more uniform.
[0072] In step S9, citric acid is slowly poured into the colloid and stirred at a speed of 200-300 rpm for 5 minutes using a low-speed stirrer. At the same time, a pH meter is used to monitor the pH value and adjusted to neutral or slightly alkaline (pH 7-8). Ensure that the pH of the solution is stable to avoid excessively high or low pH values affecting the performance of the adhesive. After the adjustment is completed, stand for 30 minutes, and the finished product, aldehyde-free high-performance plant protein adhesive, can be obtained after the bubbles are eliminated. During the standing process, pay attention to avoid air contact and maintain the sealing of the container.
[0073] In the present invention, the addition of plant-based bactericide brings significant beneficial effects to the formaldehyde-free high-performance plant protein adhesive. First, the ingredients such as tea polyphenols, aloe extract, honeysuckle extract and antibacterial silver ions in the bactericide give the adhesive excellent antibacterial properties, effectively inhibit the growth of bacteria and mold, and extend the service life of the adhesive. At the same time, the moisturizing effect of hyaluronic acid and glycerol improves the water resistance of the adhesive, ensuring that it can still maintain a stable bonding effect in a humid environment. In addition, the thickening effect of xanthan gum enhances the bonding strength of the adhesive, making it more firm during application.
[0074] In the present invention, the natural plant extracts and essential oil components in the plant-based fungicide not only improve the environmental friendliness of the adhesive, but also bring it a natural fragrance and improve the user experience. By reducing the use of chemical additives, the fungicide reduces potential health risks and makes the adhesive safer and more reliable. Overall, the addition of plant-based fungicide not only improves the comprehensive properties of the formaldehyde-free high-performance plant protein adhesive, such as antibacterial, water resistance, bonding strength and flexibility, but also extends its storage life, enhances its market competitiveness, and brings a more environmentally friendly, healthy and efficient choice to the adhesive industry.
[0075] In the present invention, the addition of silane coupling agent KH-550 has a significant improvement effect on the formaldehyde-free high-performance plant protein adhesive. First, KH-550 can effectively enhance the interfacial bonding force between the adhesive and the substrate, and through its unique chemical structure, form a strong chemical bond between the plant protein molecules and the surface of the substrate, thereby greatly improving the bonding strength and durability of the adhesive. In addition, KH-550 also has good dispersibility, which can promote the uniform distribution of fillers such as calcium carbonate in the adhesive, avoid agglomeration, and further optimize the mechanical properties and construction performance of the adhesive. Therefore, the introduction of the silane coupling agent KH-550 enables the plant protein adhesive to exhibit better bonding effect and stability in a variety of complex application environments.
[0076] In the present invention, the addition of nano zinc oxide brings additional functions and performance improvements to the formaldehyde-free high-performance plant protein adhesive. On the one hand, nano zinc oxide has excellent antibacterial properties, can effectively inhibit the microbial contamination that may occur during the use of the adhesive, and prolongs the service life and storage stability of the adhesive. On the other hand, the ultraviolet shielding effect of nano zinc oxide protects the adhesive from the influence of ultraviolet radiation, reduces the degradation reaction caused by ultraviolet rays, and thus enhances the weather resistance and aging resistance of the adhesive. In addition, the nano size effect of nano zinc oxide may also have a positive effect on the mechanical properties of the adhesive, such as improving its hardness and wear resistance. In summary, the addition of nano zinc oxide not only improves the antibacterial and weather resistance of the plant protein adhesive, but also has a beneficial effect on its long-term stability and mechanical properties, enabling it to exhibit more outstanding performance in a wider range of application fields.
[0077] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0078] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an aldehyde-free high-performance plant protein adhesive, characterized in that: The method comprises the following steps: S1: First, weigh the raw materials for preparation, and weigh: plant soybean protein powder: 100 parts by weight; water: 200-250 parts by weight; glycerin: 10-20 parts by weight; sodium hydroxide: 1-2 parts by weight; calcium carbonate: 20-30 parts by weight; urea: 5-10 parts by weight; sodium benzoate: 1-2 parts by weight; polyvinyl alcohol: 5-10 parts by weight; citric acid: 1-2 parts by weight; hyaluronic acid: 1-5 parts by weight; silane coupling agent KH-550: 1-3 parts by weight; nano zinc oxide: 1-5 parts by weight and plant-based fungicide 11-15 parts by weight; S2: Mix plant soy protein powder and water in proportion, use a high-speed mixer to stir until a uniform, particle-free protein suspension is formed, slowly add glycerol to the protein suspension, use a low-speed mixer to stir, ensure that the glycerol is completely integrated into the protein solution, and enhance the flexibility of the colloid; S3: slowly dripping sodium hydroxide solution into the above mixed solution, monitoring the pH value at the same time, adjusting it to the alkaline range, and then standing to react for 15 minutes; S4: adding calcium carbonate to the mixed solution after the reaction, and stirring with a high-speed stirrer until the calcium carbonate is evenly dispersed to form a stable suspension system; S5: adding urea, stirring with a medium-speed mixer and heating at the same time, promoting the reaction between urea and protein, and enhancing the water resistance of the adhesive; S6: After the mixed solution is cooled to room temperature, sodium benzoate and polyvinyl alcohol are added, and stirred using a high-speed stirrer until they are completely dissolved to form a uniform colloid; S7: Add hyaluronic acid to the colloid and stir with a low-speed mixer to ensure that the hyaluronic acid is evenly distributed and improve the water retention performance of the adhesive; S8: adding silane coupling agent KH-550 and nano zinc oxide, stirring with a high-speed mixer to ensure that the coupling agent and nano zinc oxide are fully dispersed to enhance the bonding strength and antibacterial properties of the adhesive; S9: Finally, add citric acid to adjust the pH value to neutral or slightly alkaline, use a low-speed mixer to stir for 5 minutes to ensure that the pH of the solution is stable, and then let it stand until the bubbles are eliminated to obtain the finished formaldehyde-free high-performance plant protein adhesive.
2. The method for preparing the formaldehyde-free high-performance plant protein adhesive according to claim 1, characterized in that: In step S1, the plant-based disinfectant includes: tea polyphenols: 15 parts by weight; aloe extract: 15 parts by weight; hyaluronic acid: 5 parts by weight; glycerin: 5 parts by weight; lavender oil: 2 parts by weight; peppermint oil: 1 part by weight; honeysuckle extract: 10 parts by weight; lemongrass oil: 2 parts by weight; antibacterial silver ions: 1-3 parts by weight; xanthan gum: 1-2 parts by weight; deionized water: 115 parts by weight; The preparation method includes: preheating deionized water to 40-50°C; adding xanthan gum, glycerin and hyaluronic acid in sequence, and stirring evenly until completely dissolved; adding tea polyphenols, aloe extract and honeysuckle extract, and continuing to stir until evenly distributed; adding antibacterial ions to ensure that they are completely dispersed in the solution; finally adding lavender oil, peppermint oil and lemongrass oil, stirring evenly and cooling to room temperature; after passing the quality inspection, packaging for use, and obtaining a plant-based disinfectant.
3. The method for preparing the formaldehyde-free high-performance plant protein adhesive according to claim 1, characterized in that: In step S2, after the protein suspension is prepared, glycerol is slowly poured into the suspension, and stirred at a speed of 300-500 rpm for 10 minutes using a low-speed stirrer; the temperature is maintained between 25-30° C. during the stirring process.
4. The method for preparing the formaldehyde-free high-performance plant protein adhesive according to claim 1, characterized in that: In the step S3, after the sodium hydroxide solution is formed, it is slowly dripped into the mixed solution in step S2, and the pH value is monitored using a pH meter to adjust to the alkaline range of pH 10-11; during the dripping process, a low-speed stirrer is used to stir at a speed of 200-300 rpm to ensure that the solution is evenly mixed; after the dripping is completed, the reaction is allowed to stand for 15 minutes to allow the solution to fully react.
5. The method for preparing the formaldehyde-free high-performance plant protein adhesive according to claim 1, characterized in that: In step S4, calcium carbonate is slowly poured into the mixed solution after the reaction, and stirred at a speed of 1000-1500 rpm for 20 minutes using a high-speed stirrer; during the stirring process, the temperature is maintained between 30-35° C. to ensure that the calcium carbonate is evenly dispersed to form a stable suspension system.
6. The method for preparing the formaldehyde-free high-performance plant protein adhesive according to claim 1, characterized in that: In step S5, urea is slowly poured into the mixed solution, and stirred at a speed of 500-700 rpm for 10 minutes using a medium-speed mixer; at the same time, the mixture is heated to 50-60° C. to promote the reaction between urea and protein, form a urea-protein complex, and enhance the water resistance of the adhesive.
7. The method for preparing the formaldehyde-free high-performance plant protein adhesive according to claim 1, characterized in that: In the step S6, after the mixed solution is cooled to room temperature, sodium benzoate and polyvinyl alcohol are slowly poured into the mixed solution, and stirred at a speed of 1000-1500 rpm for 15 minutes using a high-speed stirrer.
8. The method for preparing the formaldehyde-free high-performance plant protein adhesive according to claim 1, characterized in that: In step S7, a low-speed mixer is used to stir at a speed of 300-500 rpm for 5 minutes to ensure that the hyaluronic acid is evenly distributed and the water retention performance of the adhesive is improved; during the stirring process, the temperature is kept between 25-30°C.
9. The method for preparing the formaldehyde-free high-performance plant protein adhesive according to claim 1, characterized in that: In the step S8, a high-speed stirrer is used to stir at a speed of 1000-1500 rpm for 20 minutes to ensure that the coupling agent and nano zinc oxide are fully dispersed to form a stable nano composite material. During the stirring process, the temperature is maintained between 30-35°C.
10. The method for preparing the formaldehyde-free high-performance plant protein adhesive according to claim 1, characterized in that: In the step S9, citric acid is slowly poured into the colloid and then stirred at a speed of 200-300 rpm for 5 minutes using a low-speed stirrer; meanwhile, a pH meter is used to monitor the pH value and the pH value is adjusted to a neutral or slightly alkaline pH of 7-8.